Acute Traumatic Isolated Subluxation of Trapeziometacarpal Joint: Case Report-Literature Review - G, Kastanis; A, Pantouvaki; E, Trachanatzi; I, Stavrakakis; C, Chaniotakis; M. K., Siligardou; P., Kapsetakis (International Journal of Innovative Research in Medical Science, 2022)
Trapeziometacarpal joint (TMCJ) of the thumb is an unstable joint anatomically and depends on the integrity and normal functionality of the ligaments to prevent dislocation. Dislocation or subluxation of trapezio-metacarpal joint generally appears more often as injuries accompanied with intraarticular fracture of base of first metacarpal or trapezium. Isolated dorsolateral subluxation of trapeziometacarpal joint appears more often with osteoarthritis of the joint rather than as traumatic lesion and is an unstable injury because ligaments of the joint present some degree of impairment. Suspicions to diagnose the injury and precocious therapeutic management avoid complications which lead to impairment of hand function quality. Therapeutic procedures for TMCJ dislocation is controversial in literature. The aim of this study is to present a case of a 28 year-old man, who after a direct impact with a heavy object (hummer) over the base of the thumb, presented in the emergency department with an anterolateral subluxation of trapeziometacarpal joint and based on this case, to recall the modalities of the adequate treatment of the respective injury in literature.